WORK DEMANDS, RESOURCES, AND BURNOUT AMONG HEALTH ASSISTANTS IN SAUDI ARABIA: A MIXED METHODS STUDY - Maseer Hamdan Sayer Alharbi, Fahad Naif Naeim Alrakhimi, Khalid Bin Awad Alhumaidi Alharbi, Bader Zaben Sanhat Alharbi, Mohammed Zaben Sanhat Alharbi, Naif Shulayyil Zabn Alharbi, (Chelonian Research Foundation, 2022)
Health assistants fulfill fundamental patient care duties that are indispensable yet demanding, potentially contributing to burnout over time if unaddressed. However, minimal research examines work experiences, stressors, and burnout specifically among health assistants in Saudi Arabia. This convergent parallel mixed methods study examined work conditions, resources, demands, and burnout symptoms reported by 175 health assistants at 5 hospitals in 3 major cities. Surveys assessed demographics, job demands and resources, and burnout dimensions including emotional exhaustion, cynicism, and professional efficacy. Additionally, 8 focus groups elicited lived experiences related to workplace stressors and impacts. Key results showed high work overload was significantly associated with higher reported emotional exhaustion and cynicism. Insufficient staffing numbers, ambiguous assistant role delineations, limited autonomy, and inadequate support resources emerged as major contributing issues from qualitative accounts. Participants emphasized needs for improvements in staffing ratios, communication pathways, supervisory support, professional development, workplace culture cultivation, and increased workload flexibility. Integrated findings provide novel insights that can inform organizational interventions aimed at fostering engaged, productive, and sustainable health assistant workforces.